The use of information and distance technologies in the continuing education of teachers - Onishchenko, T. E.; Riabokon, O. V.; Korniienko, O. O.; Оніщенко, Тетяна Євгенівна; Рябоконь, Олена Вячеславівна; Корнієнко, Олена Олександрівна (My University, 2024)
Ukraine is currently developing a new education system that is focused on entering the global information and education space. This process is accompanied by significant changes in the pedagogical theory and practice of the educational process. These changes should be adequate to modern technical capabilities and contribute to the harmonious entry of the individual into the information society.